Design, synthesis, and evaluation of positron emission tomography/fluorescence dual imaging probes for targeting facilitated glucose transporter 1 (GLUT1). Issue 14 (24th March 2021) - Yuen, Richard; Wagner, Michael; Richter, Susan; Dufour, Jennifer; Wuest, Melinda; West, Frederick G.; Wuest, Frank
Abstract : We describe the synthesis and analysis of novel different glucose-based dual probes for tandem PET and fluorescent imaging of facilitated hexose transporter GLUT1 in breast cancer cells. Abstract : Increased energy metabolism followed by enhanced glucose consumption is a hallmark of cancer. Most cancer cells show overexpression of facilitated hexose transporter GLUT1, including breast cancer. GLUT1 is the main transporter for 2-deoxy-2-[ 18 F]fluoro-d -glucose (2-[ 18 F]FDG ), the gold standard of positron emission tomography (PET) imaging in oncology. The present study's goal was to develop novel glucose-based dual imaging probes for their use in tandem PET and fluorescence (Fl) imaging. A glucosamine scaffold tagged with a fluorophore and an 18 F-label should confer selectivity to GLUT1. Out of five different compounds, 2-deoxy-2-((7-sulfonylfluoro-2, 1, 3-benzoxadiazol-4-yl)amino)-d -glucose (2-FBDG ) possessed favorable fluorescent properties and a similar potency as 2-deoxy-2-((7-nitro-2, 1, 3-benzoxadiazol-4-yl)amino)-d -glucose (2-NBDG) in competing for GLUT1 transport against 2-[ 18 F]FDG in breast cancer cells. Radiolabeling with 18 F was achieved through the synthesis of prosthetic group 7-fluoro-2, 1, 3-benzoxadiazole-4-sulfonyl [ 18 F]fluoride ([ 18 F]FBDF) followed by the reaction with glucosamine. The radiotracer was finally analyzed in vivo in a breast cancer xenograft model and compared to 2-[ 18 F]FDG . Despite favourable in vitro fluorescence imaging properties, 2-[ 18 F]FBDG was found to lack metabolic stability in vivo, resulting in radiodefluorination. Glucose-based 2-[ 18 F]FBDG represents a novel dual-probe for GLUT1 imaging using FI and PET with the potential for further structural optimization for improved metabolic stability in vivo .